Spatial and sectoral roles of state-owned and private banks in Maluku’s resource financing - Sangadji, Maryam; Husen, Amran; Uar, Ningsie Indahsuary; Wahyuningsih, Diah (Asian Development Policy Review, 2026)
This study examines the role of state-owned and private banks in providing credit to the agriculture, fisheries, and mining sectors in the Maluku Islands, Indonesia, from 2010 to 2024. Although the region possesses abundant natural resources, access to financial services in remote island communities remains limited. The research aims to analyze long-term trends and spatial patterns of credit disbursement, compare sectoral financing priorities between state-owned and private banks, and assess the alignment of credit allocation with the regional economic structure. Using a descriptive-quantitative approach and secondary data from Bank Indonesia (BI), the Financial Services Authority (OJK), and the Indonesian Bureau of Statistics (BPS), three findings emerge. First, state-owned banks dominate financing with an average share of 59%, yet credit remains concentrated in administrative hubs such as Ambon City. Second, state-owned banks prioritize agriculture and fisheries, while private banks show a stronger interest in mining. Third, a mismatch persists between financing patterns and the regional economic structure, as the fisheries sector, contributing 13.66% to Gross Regional Domestic Product (GRDP), receives disproportionately low credit. These findings highlight the need for improved project-based credit reporting, spatially responsive financing policies, and stronger institutional support for productive sectors. The study contributes to the literature on spatial finance and regional development.